Respuesta :

frika

Answer:

[tex]\dfrac{1}{2x(x-1)}[/tex]

Step-by-step explanation:

Given

[tex]\dfrac{x^2+2x+1}{x^2-1}\div (2x^2+2x)[/tex]

Consider the numerator:

[tex]x^2+2x+1=(x+1)^2[/tex]

Consider the denominator:

[tex]x^2-1=(x-1)(x+1)[/tex]

Hence, the fraction becomes

[tex]\dfrac{(x+1)^2}{(x-1)(x+1)}=\dfrac{x+1}{x-1}[/tex]

Consider the expression in brackets:

[tex]2x^2+2x=2x(x+1)[/tex]

Divide:

[tex]\dfrac{x^2+2x+1}{x^2-1}\div (2x^2+2x)=\dfrac{x+1}{x-1}\div 2x(x+1)=\dfrac{x+1}{x-1}\times \dfrac{1}{2x(x+1)}=\dfrac{1}{2x(x-1)}[/tex]